The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/stem.1196
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Negatively Regulate Neurogenesis Through the Jagged1‐Mediated Notch Pathway

Abstract: Adult neurogenesis is regulated by a number of cellular players within the neurogenic niche. Astrocytes participate actively in brain development, regulation of the mature central nervous system (CNS), and brain plasticity. They are important regulators of the local environment in adult neurogenic niches through the secretion of diffusible morphogenic factors, such as Wnts. Astrocytes control the neurogenic niche also through membrane-associated factors, however, the identity of these factors and the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
127
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 55 publications
5
127
1
2
Order By: Relevance
“…We have previously shown that loss of the astrocytic intermediate filament cytoskeleton, composed of GFAP, vimentin, and nestin, affects Jagged-mediated Notch signaling during neurogenesis (13). As genes that are coexpressed in certain tissues have a higher probability to share a functional relationship (46), we screened tissue expression data in the GeneSapiens database (47) and found a strong positive correlation between the expression of vimentin and Jagged ligands in several tissues, e.g., in blood, breast, leukocytes, central nervous system, heart, kidney, muscle, and testis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that loss of the astrocytic intermediate filament cytoskeleton, composed of GFAP, vimentin, and nestin, affects Jagged-mediated Notch signaling during neurogenesis (13). As genes that are coexpressed in certain tissues have a higher probability to share a functional relationship (46), we screened tissue expression data in the GeneSapiens database (47) and found a strong positive correlation between the expression of vimentin and Jagged ligands in several tissues, e.g., in blood, breast, leukocytes, central nervous system, heart, kidney, muscle, and testis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1D). We next expressed Dll4 and Jagged, and the chimeric ligands in mouse embryonic fibroblasts (MEFs) derived from WT (VimWT) and vimentin knockout (VimKO) mice and cocultured them with 293HEK reporter cells stably expressing full-length Notch 1 (FLN reporter cells) and then measured signal activation in FLN reporter cells stably expressing full-length Notch 1 using the CSL (CBF-1, suppressor of hairless, Lag-2)-based luciferase reporter system (FLN reporter cells) (13). Transfection efficiency and expression levels of the different proteins were confirmed by immunofluorescence and Western blot (WB).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, expression of Gfap and Vim, negative regulators of neurogenesis is markedly increased in Ulk4 mutants. 22 Together, Liu et al suggest that the Wnt pathway may play a critical role in mediating the effects of Ulk4 on NSCs.…”
mentioning
confidence: 99%
“…While astrocyte secreted factors have been shown to promote neurogenesis of normal adult NSCs, astrocytes within the microenvironment of brain tumors have also been shown to promote stem-like characteristics in BTSCs and enrich the stem cell population, thus worsening the malignancy of such brain tumors [125][126][127][128]. GBM CD133 + stem cells co-cultured both directly and indirectly with astrocytes show gene expression signatures known to be involved in GBM invasion and metastasis, such as a disintegrin and metalloproteinase domaincontaining protein 10 (ADAM10), hyaluronan synthase 2 (HAS2), and vascular cell adhesion molecule-1 (VCAM1).…”
Section: Astrocytes' Direct Influence On Cancer Stem Cellsmentioning
confidence: 99%